Loan managers' decisions and trust in entrepreneurs in different institutional contexts - Moro, Andrea; Fink, Matthias; Maresch, Daniela; Fredriksson, Antti (Taylor & Francis, 2017)
Loan managers’ trust in entrepreneurs can be a useful tool for overcoming entrepreneurial firms’ opaqueness. Nevertheless, the possibility for loan managers to leverage trust can be affected by differences in the regulative institutions within the banks (type of bank) and by place-bound normative institutions (social context). By relying on semi-structured interviews and a survey of 450 bank-entrepreneur relationships, this study finds that a positive impact of trust in lending relationships is sensitive to different place-bound normative institutions and to the regulative institutions within the banks. The results are robust with respect to potential endogeneity issues.
Keywords: Bank credit; Relationship lending; Small and medium enterprises; Trust; Institutional embeddedness